Bactericidal properties of plants-derived metal and metal oxide nanoparticles (NPs) - Teow, Sin Yeang *; Wong, Magdelyn Mei Theing *; Yap, Hooi Yeen *; Peh, Suat Cheng *; Shameli, Kamyar (MDPI, 2018)
Nanoparticles (NPs) are nano-sized particles (generally 1–100 nm) that can be synthesized through various methods. The wide range of physicochemical characteristics of NPs permit them to have diverse biological functions. These particles are versatile and can be adopted into various applications, particularly in biomedical field. In the past five years, NPs’ roles in biomedical applications have drawn considerable attentions, and novel NPs with improved functions and reduced toxicity are continuously increasing. Extensive studies have been carried out in evaluating antibacterial potentials of NPs. The promising antibacterial effects exhibited by NPs highlight the potential of developing them into future generation of antimicrobial agents. There are various methods to synthesize NPs, and each of the method has significant implication on the biological action of NPs. Among all synthetic methods, green technology is the least toxic biological route, which is particularly suitable for biomedical applications. This mini-review provides current update on the antibacterial effects of NPs synthesized by green technology using plants. Underlying challenges in developing NPs into future antibacterials in clinics are also discussed at the present review.